2018
DOI: 10.7557/2.38.1.4124
|View full text |Cite
|
Sign up to set email alerts
|

Does connectivity exist for remnant boreal caribou (Rangifer tarandus caribou) along the Lake Superior Coastal Range? Options for landscape restoration

Abstract: Genetic analysis can provide important information on the dynamic and spatial structure of groups of animals or populations. Little is known of the genetic population structure of caribou that inhabit the Lake Superior Coastal Range (LSCR) and the level of gene flow between individuals within the range and beyond. From a landscape perspective, this range is spatially isolated and genetic connectivity within the range is presumed limited due to large water crossings on Lake Superior. This study aims to answer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…This dataset was assembled primarily from caribou fecal samples collected during winters of 2005-2011. Island populations (i.e., Slate Islands, Michipicoten Island, and Pic Island) were not included in this study as they are isolated, disjoint from the continuous mainland distribution and experiencing genetic drift (Drake et al, 2018). Fecal samples collected during the winter generally produced relatively high yields of DNA (Ball et al, 2007), which minimized genotyping error rates (see Hettinga et al, 2012).…”
Section: Study Area and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…This dataset was assembled primarily from caribou fecal samples collected during winters of 2005-2011. Island populations (i.e., Slate Islands, Michipicoten Island, and Pic Island) were not included in this study as they are isolated, disjoint from the continuous mainland distribution and experiencing genetic drift (Drake et al, 2018). Fecal samples collected during the winter generally produced relatively high yields of DNA (Ball et al, 2007), which minimized genotyping error rates (see Hettinga et al, 2012).…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…Fecal samples collected during the winter generally produced relatively high yields of DNA (Ball et al, 2007), which minimized genotyping error rates (see Hettinga et al, 2012). Island populations (i.e., Slate Islands, Michipicoten Island, and Pic Island) were not included in this study as they are isolated, disjoint from the continuous mainland distribution and experiencing genetic drift (Drake et al, 2018).…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…Notably, the caribou from Cochrane has undergone less inbreeding than the other Ontario boreal caribou sampled and had the least IBD ROH with the Michipicoten Island caribou. Previous research based on microsatellite data suggested Michipicoten Island and Pukaskwa National Park belong to a different genetic cluster than the nearby boreal caribou from Cochrane (Drake et al, 2018).…”
Section: Inbreeding Historiesmentioning
confidence: 90%
“…Caribou disappeared from the park in 2011, and reappeared in 2015, perhaps due to colonization from one of the Lake Superior islands. One of the last caribou captured on wildlife cameras deployed in Pukaskwa National Park had small, malformed antlers, which was suggested to be a sign of inbreeding (Drake et al, 2018). Currently, there are no caribou in the park and the population is considered potentially extirpated.…”
Section: Caribou Samplingmentioning
confidence: 99%
See 1 more Smart Citation